Stres Kerja Perawat Psikiatri di Ruang Rawat Inap Rumah Sakit Jiwa - Sri Novitayani; Mirna Deviana; Irfanita Nurhidayah (Poltekkes Kemenkes Maluku, 2021)
Psychiatric nursing is considered one of the most stressful jobs in the world. 1 to 3 medical workers in the department of psychiatry have been reported to have higher fatigue levels than medical workers in other departments. This study aimed to determine the level of work stress of psychiatric nurses in the Mental Hospital. This type of research is descriptive. The sampling technique used purposive sampling of as many as 83 nurses from 12 inpatient rooms at the Aceh Mental Hospital with the criteria of implementing nurses, marital status, D3, and S1 education, nurses on duty, and willing to be respondents in this study. The instrument used to measure work stress is The Workplace Stress Scale which contains 8 statement items with 5 Likert scales. The results showed that the majority of respondents were in the category of severe stress (32.5%) followed by moderate stress (28.9%), potentially dangerous (24.1%), and mild stress (14.5%). Work stress on psychiatric nurses in the Aceh Mental Hospital inpatient room is in the category of severe stress. It is recommended that the hospital increase cooperation between nurses and other health workers and clarify the duties of nurses to reduce work stress on psychiatric nurses.